Organic-matter quality of deep permafrost carbon - Strauss, Jens (Dr.); Schirrmeister, Lutz (Dr.); Mangelsdorf, Kai (Dr.); Eichhorn, L.; Wetterich, Sebastian; Herzschuh, Ulrike (Prof. Dr.) (2019)
The organic-carbon (OC) pool accumulated in Arctic permafrost (perennially frozen ground) equals the carbon stored in the modern atmosphere. To give an idea of how Yedoma region permafrost could respond under future climatic warming, we conducted a study to quantify the organic-matter quality (here defined as the intrinsic potential to be further transformed, decomposed, and mineralized) of late Pleistocene (Yedoma) and Holocene (thermokarst) deposits on the Buor-Khaya Peninsula, northeast Siberia. The objective of this study was to develop a stratigraphic classified organic-matter quality characterization. For this purpose the degree of organic-matter decomposition was estimated by using a multiproxy approach. We applied sedimentological (grain-size analyses, bulk density, ice content) and geochemical parameters (total OC, stable carbon isotopes (delta C-13),total organic carbon : nitrogen (C / N) ratios) as well as lipid biomarkers (n-alkanes, n-fatty acids, hopanes, triterpenoids, and biomarker indices, i.e., average chain length, carbon preference index (CPI), and higher-plant fatty-acid index (HPFA)). Our results show that the Yedoma and thermokarst organic-matter qualities for further decomposition exhibit no obvious degradation-depth trend. Relatively, the C / N and delta C-13 values and the HPFA index show a significantly better preservation of the organic matter stored in thermokarst deposits compared to Yedoma deposits. The CPI data suggest less degradation of the organic matter from both deposits, with a higher value for Yedoma organic matter. As the interquartile ranges of the proxies mostly over-lap, we interpret this as indicating comparable quality for further decomposition for both kinds of deposits with likely better thermokarst organic-matter quality. Supported by principal component analyses, the sediment parameters and quality proxies of Yedoma and thermokarst deposits could not be unambiguously separated from each other. This revealed that the organic-matter vulnerability is heterogeneous ...